2017
DOI: 10.4103/2045-9912.202910
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection provided by isoflurane pre-conditioning and post-conditioning

Abstract: Isoflurane, a volatile and inhalational anesthetic, has been extensively used in perioperative period for several decades. A large amount of experimental studies have indicated that isoflurane exhibits neuroprotective properties when it is administrated before or after (pre-conditioning and post-conditioning) neurodegenerative diseases (e.g., hypoxic ischemia, stroke and trauma). Multiple mechanisms are involved in isoflurane induced neuroprotection, including activation of glycine and γ-aminobutyric acid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Isoflurane administration during i.t. procedures can complicate the interpretation of our results since isoflurane has been shown to have both neuroprotective and neurotoxic affects (Jiang et al, 2017). Isoflurane pretreatment has been implicated as having protective effects in ischemia in animal models (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflurane administration during i.t. procedures can complicate the interpretation of our results since isoflurane has been shown to have both neuroprotective and neurotoxic affects (Jiang et al, 2017). Isoflurane pretreatment has been implicated as having protective effects in ischemia in animal models (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…procedures can complicate the interpretation of our results since isoflurane has been shown to have both neuroprotective and neurotoxic affects (Jiang et al, 2017). Isoflurane pretreatment has been implicated as having protective effects in ischemia in animal models (Jiang et al, 2017). In animal models of neural injury in neonatal rats, isoflurane was shown to decrease the hypoxia-related increase in the release of amino acid neurotransmitters while elevating levels of GABA (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the choice of anesthetic regimen is crucial when performing stroke surgery in rodents, as it can strongly influence CBF and stroke outcome, and may contribute to translational failure ( O’Collins et al, 2006 ). For instance, isoflurane is a potent vasodilator with neuroprotective effects ( Tsuda, 2010 ; Gaidhani et al, 2017 ; Jiang et al, 2017 ; Lu et al, 2017 ) via modulation of eNOS activity ( Kehl et al, 2002 ; Krolikowski et al, 2006 ), which strongly confounds results. Ketamine/Xylazine (K/X) anesthesia affects baseline CBF to a lesser extent, but has also been shown to modulate eNOS ( Chen et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the use of ISO during surgery is considered optimal for neuroprotection ( 47 ). ISO post-conditioning notably decreases the infarct volume and improves the neurobehavioral performance of rats subjected to middle cerebral artery occlusion, thereby providing increased ischemic tolerance in the brain ( 48 ).…”
Section: Discussionmentioning
confidence: 99%